The influence of nutritional literacy and adolescent eating habits: A literature review - Fikroh, Yadya'ul; Nurjanah, Nurjanah; Rimawati, Eti; Yuantari, MG Catur; Khoironi, Adian (Institute of Computer Science (IOCS), 2025)
Adolescents are prone to nutrition problems due to low nutrition literacy and unhealthy eating patterns. In Indonesia, the prevalence of chronic energy deficiency (CED), central obesity, and anemia in adolescents is still high, potentially increasing infectious diseases in adulthood. The literature review method was used in this study through a systematic search through BioMed, Googe Scholar, Pubmed, Science Direct, and SAGE databases. Articles that met the inclusion criteria and were published between 2020-2024 and were relevant to nutrition literacy, eating habits, and nutritional status of adolescents were further analyzed. Analysis of the 7 selected articles showed that good nutrition literacy was positively associated with healthier food choices. However, good nutrition literacy is not sufficient without a supportive environment and behavioral skills. Nutritional literacy and adolescent diets are influenced by factors such as socioeconomic status, maternal education, and access to health services. A comprehensive approach through school education, family roles, and policies that contribute to improving nutrition literacy in adolescents is needed. Preventing obesity and non-communicable diseases in the future is important by strengthening nutrition literacy. Prioritizing applicable skills such as healthy cooking, and reading food labels in support of sustainable behavior change is recommended for future interventions.